La ilustración como medio de difusión cultural en la parroquia San Buenaventura: mitos y leyendas. - Elizalde Castillo, Melanie Paulette (2023)
The objective of this study is to design an editorial product with graphic illustration techniques and digital layout for the cultural diffusion of eos and legends in the San Buenaventura parish. During the research process, it was possible to detect the scarcity of information about the myths and legends in the San Buenaventura parish, due to the fact that the community itself does not have knowledge about its own traditions and oral expressions. For the resolution of this problem, it was decided to make an artbock on the myths and legends of the town together with main information about the community. This editorial proposal is based on Bruce Archer's methodology, where 3 phases are applied for the process of its realization, the first analytical phase, which is solved through bibliographic and field research, this with the help of the inhabitants, the second creative phase, resolved through the realization of the sketch and illustration of the editorial product, and the last executive phase, carried out through the layout of the artbook.